Quality Control Analysis Using the Failure Mode and Effect Analysis Method: Analisis Pengendalian Kualitas Menggunakan Metode Failure Mode and Effect Analysis - Hakim, Muchammad Lukman; Cahyana, Atikha Sidhi (Procedia of Engineering and Life Science, 2024)
This study aims to identify critical factors contributing to defects in Epodion rh-Erythropoietin Alfa syringes and propose strategies to minimize production flaws. Through Failure Modes and Effect Analysis (FMEA), the research identified cracking as the predominant defect, accounting for 43 out of 62 observed syringe flaws in a production batch of 162,332 units. The Risk Priority Number (RPN) calculation yielded a score of 162, indicating material-related issues as the primary concern. Consequently, the study recommends stringent quality testing of raw materials to enhance material strength and diminish product defects, thereby bolstering overall manufacturing quality. Highlights : The study aimed to investigate factors contributing to defective Epodion® rh-Erythropoietin Alfa syringes, with a focus on reducing cracks during manufacturing. A Failure Mode and Effect Analysis (FMEA) approach was used to identify the primary causes of failure, revealing cracking as the predominant issue affecting 43% of defective units. Enhanced quality control measures for raw materials prior to their utilization within the production process were recommended to minimize product defects. Keywords: Epodion, rh-Erythropoietin Alfa, syringes, FMEA, quality control.